Dynamic Knee Alignment and Collateral Knee Laxity and Its Variations in Normal Humans - Deep, Kamal; Picard, Frederic; Clarke, Jon V. (Frontiers in Surgery, 2015)
Alignment of normal, arthritic and replaced human knees is a much debated subject as is the collateral ligamentous laxity. Traditional quantitative values have been challenged. Methods used to measure these are also not without flaws. Authors review the recent literature and a novel method of measurement of these values has been included. This method includes use of computer navigation technique in clinic setting for assessment of the normal or affected knee before the surgery. Computer navigation has been known for achievement of alignment accuracy during knee surgery. Now its use in clinic setting has added to the inventory of measurement methods. Authors dispel the common myth of straight mechanical axis in normal knees and also look at quantification of amount of collateral knee laxity. Based on the scientific studies it has been shown that the mean alignment is in varus in normal knees. It changes from lying non weight bearing position to standing weight bearing position in both coronal and the sagittal planes. It also varies with gender and race. The collateral laxity is also different for males and females. Further studies are needed to define the ideal alignment and collateral laxity which the surgeon should aim for individual knees.